P102 NEW THREE–DIMENSIONAL ECHOCARDIOGRAPHIC PREDICTING PARAMETERS IN TRANS–VENTRICULAR HEART–BEATING MITRAL VALVE REPAIR WITH NEOCHORDAE: A MONOCENTRIC RETROSPECTIVE STUDY. (18th May 2022) - Gaiero, L; Vairo, A; Fioravanti, F; Piroli, F; Gallone, G; D'Ascenzo, F; Desalvo, P; Marro, M; Sebastiano, V; Alunni, G; De Ferrari, G; Rinaldi, M; et al.
Abstract: Background: Trans–ventricular off pump mitral valve (MV) repair with neochordae implantation (Neochord procedure) is a minimally invasive surgical technique for correction of degenerative mitral regurgitation (MR) due to prolapse or flail. The aim of this study was to evaluate mid–term results of patients undergoing this procedure and find new three–dimensional pre–operative echocardiographic parameters to predict MR recurrence at follow–up. Methods: We performed a retrospective analysis of 72 consecutive patients with severe MR due to prolapse or flail who underwent Neochord procedure at our hospital from March 2015 to February 2021. MV pre–operative anatomical parameters were assessed using 2D TEE, 3D TEE and dedicated three–dimensional (3D) post–processing analysis with dedicated software (QLAB, Philips). TTE follow–up and clinical evaluation were performed at 3 months, 6 months, 1 year and then annually. Results: Twenty–seven patients were female (37.5%), mean age was 77±9 years. The average preoperative EuroSCORE II was 2.2%±1.5%. Twenty–three patients (32%) had an history of paroxysmal or persistent atrial fibrillation. Procedural success at discharge was achieved in sixty–eight patients (94.5%). Mean follow–up was 30±16 months. Three years follow–up was completed by fifty patients. At three years thirteen patients (26%) presented with recurrence of severe MR or underwent new surgical operation. Prevalence of mild or trace MR at three years follow–up visit was 70%. End–systolic annulus area (12.5±2.5 cm2 vs 14.1±2.6 cm2; p = 0.038), end–systolic annulus diameter (13.2±1.2 cm vs 14±1.3 cm; p = 0.042) and indexed left atrial volume (59±17 ml/m2 vs 76±37 ml/m2; p = 0.041) were lower in patients with residual MR less than moderate (MR < 3+/4+). Three–dimensional indexes specifically focused on coaptation reserve and annular disfunction were the best predictors of MR < 3+/4+ at follow–up, in particular diastolic sum of the leaflets/end–systolic annulus area ([AUC] 0.74; p = 0.029) and systo–diastolic annulus area fractional change ([AUC] 0.743; p = 0.035). Furthermore, each of these annular parameters, calculated using dedicated 3D software, were predictive of residual MR, whereas annular 2D dimensions were not (p = 0.347). Conclusion: In patients with degenerative MR treated with Neochord procedure, 3D analysis focused on annular measures and coaptation indexes, that included 3D annular dimensions, predicts better MR relapse than conventional 2D parameters.